Retrograde nerve growth factor signaling modulates tooth mechanical hyperalgesia induced by orthodontic tooth movement via acid-sensing ion channel 3 - Meiya Gao; Xinyu Yan; Yanzhu Lu; Linghuan Ren; Shizhen Zhang; Xiaoqi Zhang; Qianyun Kuang; Lu Liu; Jing Zhou; Yan Wang; Wenli Lai; Hu Long (Nature Publishing Group, 2021)
Abstract Orthodontic tooth movement elicits alveolar bone remodeling and orofacial pain that is manifested by tooth mechanical hyperalgesia. Nerve growth factor (NGF) is upregulated in periodontium and may modulate tooth mechanical hyperalgesia. The objectives were to examine the role of NGF in tooth mechanical hyperalgesia and to elucidate the underlying mechanisms. Tooth mechanical hyperalgesia was induced by ligating closed coil springs between incisors and molars in Sprague-Dawley rats. Retrograde labeling was performed by periodontal administration of fluor-conjugated NGF and the detection of fluorescence in trigeminal ganglia (TG). Lentivirus vectors carrying NGF shRNA were employed to knockdown the expression of NGF in TG. The administration of agonists, antagonists, and virus vectors into TG and periodontium was conducted. Tooth mechanical hyperalgesia was examined through the threshold of biting withdrawal. Our results revealed that tooth movement elicited tooth mechanical hyperalgesia that could be alleviated by NGF neutralizing antibody and that NGF was upregulated in periodontium (mainly in periodontal fibroblasts) and TG. Retrograde labeling revealed that periodontal NGF was retrogradely transported to TG after day 1. Acid-sensing ion channel 3 (ASIC3) and NGF were co-expressed in trigeminal neurons and the percentage of co-expression was significantly higher following tooth movement. The administration of NGF and NGF neutralizing antibody into TG could upregulate and downregulate the expression of ASIC3 in TG, respectively. NGF aggravated tooth mechanical hyperalgesia that could be alleviated by ASIC3 antagonist (APETx2). Moreover, NGF neutralizing antibody mitigated tooth mechanical hyperalgesia that could be recapitulated by ASIC3 agonist (GMQ). NGF-based gene therapy abolished tooth mechanical hyperalgesia and downregulated ASIC3 expression. Taken together, in response to force stimuli, periodontal fibroblasts upregulated the expressions of NGF that was retrogradely transported to TG, where NGF elicited tooth mechanical hyperalgesia through upregulating ASIC3. NGF-based gene therapy is a viable method in alleviating tooth-movement-induced mechanical hyperalgesia.